Systems for Arctic Spill Response - Schultz, L. A.; Deslauriers, Paul C.; DeBord, F. W.; Voelker, R. P. (United States. Coast Guard. Office of Research and Development., 1978)
Abstract: This final report summarizes the work accomplished under Phase I of the program entitled "Study to Define Arctic Pollution Response Systems and Develop Arctic Oil Pollution Response Project Plans."